2006
DOI: 10.1007/s10157-006-0441-8
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic-adsorbent AST-120 reduces overload of indoxyl sulfate and the plasma level of TGF-β1 in patients with chronic renal failure

Abstract: These results support the notion that indoxyl sulfate and TGF-beta1 may be involved in the progression of CRF, and that the oral adsorbent AST-120 may suppress the progression, at least in part, by reducing overproduction of TGF-beta1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 21 publications
4
16
0
Order By: Relevance
“…Most studies reported the effect in lowering indoxyl sulfate and the decrease by AST-120 is dose-dependent [18]. Similar to the dose we used in the present study, a reduction rate of indoxyl sulfate was 11-34% in previous studies [17,18,19]. Only one study investigated the effect of AST-120 in HD patients [13].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Most studies reported the effect in lowering indoxyl sulfate and the decrease by AST-120 is dose-dependent [18]. Similar to the dose we used in the present study, a reduction rate of indoxyl sulfate was 11-34% in previous studies [17,18,19]. Only one study investigated the effect of AST-120 in HD patients [13].…”
Section: Discussionsupporting
confidence: 61%
“…It is therefore necessary to develop a strategy to prevent the production or reduce the burden of uremic retention compounds. AST-120 is an oral adsorbent that is able to inhibit intestinal absorption of protein-bound uremic toxins and thus can reduce their blood levels [17,18,19,20]. One recent study found that AST-120 can even attenuate the disruption of the tight junction of colon epithelia cells [21].…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Administration of IS also accelerated the aggravation of renal fibrosis, whereas treatment to decrease IS level resulted in a stabilization of renal function. 3,6,20 One of the most important findings of this study was an induction of EMT by IS, which was confirmed by morphological transition and cell migration of cultured murine EMT. 11,12 The presence of EMT in renal fibrosis was first demonstrated by Strutz et al, 21 and confirmed by others in in vivo and in vitro experiments.…”
Section: Discussionmentioning
confidence: 66%
“…probiotics, prebiotics and dietary modification) and adsorbent therapies that bind precursors of the various uremic retention solutes in the intestines to reduce their absorption. Several studies have indicated retardation of CKD progression by AST-120, an orally ingested activated charcoal adsorbent [32,33,34,35,36]. …”
Section: Discussionmentioning
confidence: 99%